THE “DISPATCH OF EDUCATION” TO “RURAL COMMUNITIES” FOR “NATIONAL UNITY” - THE MAGICAL BUZZWORDS OF CULTURAL GENOCIDE - Marcello Messina (Nepan editor, 2019)
In July 2017, as delegates of the Universidade Federal do Acre we were invited to talk at the I Seminario Internacional de Educación Rural in Peru, in the cities of Lircay and Lima. In this article, we focus specifically on the debate that took place in Lima, in order to identify epiphanic passages that expose crucial conceptions of “rural” and “bilingual” education and unearth the ways in which these concepts are used as disguising paraphrases meant to depoliticise and efface Indigeneity together with its profound political significance. In order to accomplish this task, we draw upon an unsystematic approach to some principles of corpus linguistics, and combine our first-hand impressions with a review of Peruvian and non-Peruvian literature on the political implications of Indigeneity. We then conclude by identifying a substantially undeclared agenda that envisages the “pacific” and “painless” perpetuation of an ongoing cultural genocide.